2011
DOI: 10.1128/jb.05187-11
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Regulation of the yefM-yoeB Toxin-Antitoxin Locus of Streptococcus pneumoniae

Abstract: Type II (proteic) toxin-antitoxin systems (TAS) are ubiquitous among bacteria. In the chromosome of the pathogenic bacterium Streptococcus pneumoniae, there are at least eight putative TAS, one of them being the yefM-yoeB Spn operon studied here. Through footprinting analyses, we showed that purified YefM Spn antitoxin and the YefM-YoeB Spn TA protein complex bind to a palindrome sequence encompassing the ؊35 region of the main promoter (P yefM2 ) of the operon. Thus, the locus appeared to be negatively autore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 53 publications
(59 reference statements)
1
67
0
Order By: Relevance
“…The influence of the BOX subelement boxAC on the expression of the yefM-yoeB TAS of S. pneumoniae was reported recently by our laboratory (21); this boxAC is highly conserved in all the S. pneumoniae strains that harbor the yefM-yoeB TAS. In the strains that we studied here, BOX elements were annotated in only two instances, R6 and ATCC 700669.…”
Section: The Enigmatic Box Elementsmentioning
confidence: 97%
See 4 more Smart Citations
“…The influence of the BOX subelement boxAC on the expression of the yefM-yoeB TAS of S. pneumoniae was reported recently by our laboratory (21); this boxAC is highly conserved in all the S. pneumoniae strains that harbor the yefM-yoeB TAS. In the strains that we studied here, BOX elements were annotated in only two instances, R6 and ATCC 700669.…”
Section: The Enigmatic Box Elementsmentioning
confidence: 97%
“…Instead, transcriptional fusion assays indicated that the presence of boxAC (P yefM1 ) together with P yefM2 and the yefM reading frame in cis led to transcriptional activation in E. coli. It was suggested that activation could be due to still unknown host binding factors and/or other cis-acting elements (21). The presence of this boxAC element is universal, as it is found in all sequenced pneumococcal strains that harbor an intact yefM-yoeB locus but is absent in other yefM-yoeB homologues of different bacteria.…”
Section: Genetic Organization and Transcriptional Regulationmentioning
confidence: 99%
See 3 more Smart Citations